Transparansi Informasi Label Gizi dan Pengetahuan Gizi pada Kemasan terhadap Keputusan Pembelian - Mochammad Akbar (Yayasan Literasi Sains Indonesia, 2026)
The increased use of packaged food and beverage goods, the information on the packaging has become one of the most important factors for customers to consider when making purchasing decisions. The clarity of nutrition label information, as well as customer awareness of nutrition, are important factors in assisting consumers in selecting safer and healthier goods. The purpose of this study is to investigate the impact of nutrition label transparency and nutritional knowledge on food and beverage purchasing decisions. The study employed a survey method with a quantitative approach. Data was collected by distributing online questionnaires to 66 respondents chosen using a purposive selection technique. Validity and reliability tests, classical assumption tests, and multiple linear regression analysis were used to analyze the data. The findings revealed that transparency of nutrition label information and nutritional awareness had a positive and significant impact on both individual and group purchase decisions. The coefficient of determination of 74.3% implies that both variables contribute significantly to explaining differences in consumer purchasing decisions.